IMPLEMENTASI QR-CODE UNTUK SISTEM PEMESANAN MAKANAN PADA FOOD COURT KARMEL - Putra, Alrezky Irawan (Jurnal Ilmu Komputer dan Sistem Informasi, 2017)
Restaurant Food Court Karmel still doing food ordering manually. To improve service quality, to simplify the booking process and move the calculation of the amount of payment required restaurant patrons applications in order to help that goal. In this regard, the Food Court Carmel implement application-based food ordering system QR-Code. Applications developed also includes features that provide information menus were booked into the kitchen, so as to facilitate the delivery of the order information between the cashier and the kitchen section. This application can simplify the delivery of information between the cashier food menu and the kitchen, as well as facilitate food orders and payments quickly and practically. Results of testing the QR-Code Scanner has been in line with expectations of the manufacturer of the application, for the dull paper scanner can read the entire laptop up to 100%, while the soiled paper can be read up to 90% of success, and for damaged paper can be read up to 90% success. For testing QR-Code with various sizes can read up 87.5% success. For testing QR-Code with various resolutions can be read up to 80% success.